Pembangunan Aplikasi Manajemen Tugas Mahasiswa Berbasis Mobile Android - afwan, zul; kurniawan, wahyu joni; putra, pandu pratama (STIKOM Tunas Bangsa Pematangsiantar, 2017)
The task of the student is one of the assessment of student learning outcomes, the students who do not collect the task due to forgetting or not knowing the duty of the lecturer is very detrimental to the students. The tasks collected with the softcopy type sometimes troubled the students in collecting and also making it difficult for the lecturers to make all student assignments. By utilizing technology in supporting the lectures, mobile applications that are built to help students and lecturers in the lecture. Applications are built consisting of two sides, the first web application that will be used lecturers concerned in managing student tasks. Second, mobile-based applications that will be paired to student mobile devices that will interact with lecturers.